1992
DOI: 10.1254/jjp.59.89
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Antinephritic Effects of Plant Components (3): Effect of Pachyman, a Main Component of Poria Cocos Wolf on Original-Type Anti-GBM Nephritis in Rats and Its Mechanisms

Abstract: ABSTRACT-The antinephritic effect of pachyman on original-type anti-GBM nephritis in rats was in vestigated. Pachyman was given to original-type anti-GBM nephritic rats for 10 days from the day of anti-GBM serum injection. Pachyman prevented urinary protein excretion and the elevation of serum cholesterol content. Histopathological observations of the glomeruli indicated that although the number of nuclei and adhesion to capillary walls of Bowman's capsule in nephritic control rats were significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…We previously reported that mizoribin and Aza, an im munosuppressive agent (7), inhibited the elevation of plas ma antibody against rabbit IgG and Pachyman, a main component of Poria cocos (18), decreased the degree of C3 deposition on the GBM, and both were markedly effec tive against anti-GBM nephritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that mizoribin and Aza, an im munosuppressive agent (7), inhibited the elevation of plas ma antibody against rabbit IgG and Pachyman, a main component of Poria cocos (18), decreased the degree of C3 deposition on the GBM, and both were markedly effec tive against anti-GBM nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…7) Original-type anti-GBM nephritis was induced in rats by injection of 0.6 ml of anti-GBM serum into their tail veins, as described previously (18). Nephritic rats were pretreated and posttreated with ACT at 30 mg/kg, p.o.…”
Section: Effect Of Act In Crescentic-type Anti-gbm Nephritismentioning
confidence: 99%
“…31 Hoelen, Citri Unshiu Pericarpium, Agastachis Herba, Spatholobi Caulis, Rhynchosia Nulubilis and Glycyrrhizae Radix have anti-inflammatory activity as immune modulators. [35][36][37][38][39][40] Hoelen blocks selective serotonin reuptake inhibitors (SSRIs), which can induce anorexia with serotonin, and Pinelliae inhibits the vomiting center in animal models. 43,44 Appetite, body weight, and survival are endpoints for anorexia management in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The current herbal decoction, which includes Astragali Radix, [31][32][33][34] Atractylodis Rhizoma Alba, Hoelen, [35][36][37][38] Pinelliae Tuber, Citri Unshiu Pericarpium, 39 Agastachis Herba, 40 Alismatis Rhizoma, Plantaginis Semen, 41 Spatholobi Caulis, 42 Zizyphi Fructus, Rhynchosia Nulubilis, Crataegi Fructus, Galli Stomachichum Corium, and Glycyrrhizae Radix, is an immune modulator, is renoprotective, reduces lactate dehydrogenase, and increases gastrointestinal function. [43][44][45][46] This mixture has been developed to improve gastrointestinal function and modulate the immune system to treat anorexia.…”
Section: Introductionmentioning
confidence: 99%
“…Other therapeutic effects include promotion of reticulo-endothelial activity, anticomplementary action and improve ment of immune functions [21][22][23]. The other component Pori a cocos has been shown to suppress tumor necrosis factor a, interleukin 1(5, interleukin 6 and granulocytemonocyte colony-stimulating factor secretion from hu man monocytes [24], The extract also exhibited antinephritic effects [25], Paeonia suffruticosa, on the other hand, demonstrated radical scavenging and anti-oxida tive effects [26],…”
Section: Discussionmentioning
confidence: 99%